Selected topics in advanced solid state and fibre optic sensors - Vaezi-Nejad, S. M. (S. Mortaza) (Institution of Engineering and Technology, 2000)
The following topics are dealt with: optical measurement systems; fibre optic sensors; dielectrophoretic sensors; electrically conducting polymer sensors; chemical sensors; microbiological applications; and thin film phthalocyanine gas sensors.